Deterent Waste Conductivity in Producing Electricity - Asti Riani Putri; Anggara Sukma Ardiyanta; Anang makruf (Department of Electrical Engineering ITS and FORTEI, 2019)
The importance of socialization about alternative energy that can be used for daily needs, for example from the simplest such as lighting at home, although not permanent but is very useful in the event of a sudden power outage. The high price of electricity makes small communities have to think twice as much to regulate daily expenditure needs so as to encourage to find alternative energy that can produce electricity that is environmentally friendly. Seeing the large number of detergent products in Indonesia, it inspires to process the waste from laundry clothes or other objects and even the detergent water itself, because so far the used laundry waste is thrown away so that it can pollute the environment. The purpose of this study is to reduce the effect of environmental pollution due to used laundry waste which is used as an alternative energy source to turn on lighting lamps at home or even on the road. The method used in this research is a chemical or electrolysis reaction involving zinc and carbon as well as the content in detergent washing water. From several experiments conducted for 3 detergents with several parameters, namely the amount of mass and water volume of 120 ml. From the experiment the voltage is 1 volt with a current of 2 mA for detergent Rinso, for DAIA detergent the voltage is 0.7 and current is 0.56 mA, and the experiments tested on SOKLIN produce a voltage of 0.8 volt and a current of 1 mA. Whereas the testing which was carried out randomly with a volume of 1200 ml water produced a voltage of 0.547 v with a large current of 0.006 mA. This proves that detergent waste can be utilized as a renewable energy although it still requires further research but this can ease the burden on the community to pay for electricity from PLN and in the subsequent development independent power plants are built in each house so that the community can save on electricity.Keywords: alternative energy, detergent, electricity.